Binding of alpha-bungarotoxin to proteolytic fragments of the alpha subunit of Torpedo acetylcholine receptor analyzed by protein transfer on positively charged membrane filters. - Wilson, P T (1984)
Proteolytic fragments of the alpha subunit of the acetylcholine receptor retain the ability to bind alpha-bungarotoxin following resolution by polyacrylamide gel electrophoresis and immobilization on protein transfers. The alpha subunit of the acetylcholine receptor of Torpedo electric organ was digested with four proteases: Staphylococcus aureus V-8 protease, papain, bromelain, and proteinase K. The proteolytic fragments resolved on 15% polyacrylamide gels were electrophoretically transferred onto positively charged nylon membrane filters. When incubated with 0.3 nM 125I-labeled alpha-bungarotoxin and autoradiographed, the transfers yielded patterns of labeled bands characteristic for each protease. The molecular masses of the fragments binding toxin ranged from 7 to 34 kDa, with major groupings in the 8-, 18-, and 28-kDa ranges. The apparent affinity of the fragments for alpha-bungarotoxin as determined from the IC50 value was 6.7 X 10(-8) M. The labeling of fragments with alpha-bungarotoxin could be inhibited by prior affinity alkylation of receptor-containing membranes with 4-(N-maleimido)-alpha-benzyltrimethylammonium iodide. These findings demonstrate that immobilized proteolytic fragments as small as 1/5 the size of the alpha subunit retain the structural characteristics necessary for binding alpha-bungarotoxin, although the toxin is bound to the fragments with lower affinity than to the native receptor. The effect of affinity ligand alkylation demonstrates that the alpha-bungarotoxin binding site detected on the proteolytic fragments is the same as the affinity-labeled acetylcholine binding site on the intact acetylcholine receptor.